Bioavailability-Enhanced Nanoemulsion of Andrographolide for Oral Delivery: A Novel Antiviral Drug Delivery Strategy – A Research Study - Kumar, Chandan; Hasan, Chowdhury Hasibul; Singh, Kanchan (Journal of Neonatal Surgery, 2025)
Background: Andrographis paniculata is a medicinal herb widely recognized for its broad-spectrum antiviral activity, primarily due to the presence of andrographolide. However, its therapeutic potential is significantly limited by poor water solubility, low oral bioavailability, and rapid metabolism. Objective: This study aimed to formulate and evaluate a stable nanoemulsion-based oral syrup containing andrographolide to enhance its solubility, bioavailability, and antiviral efficacy. Methods: Andrographolide was extracted from A. paniculata using microwave-assisted extraction (MAE). A nanoemulsion was prepared using castor oil (oil phase), Tween 80 (surfactant), and propylene glycol (co-surfactant), followed by high-speed homogenization and ultrasonication. The formulation was evaluated for particle size, zeta potential, size distribution (polydispersity index), pH, viscosity, preliminary phytochemical evaluation, terpenoid content in extract and appearance. Results: The developed nanoemulsion had an average droplet size of 191.1 nm and a zeta potential of –31.5 mV, indicating good stability. The pH between 5.5 and 7.0 and viscosity (75.7 cP) were within the acceptable range for oral administration. Phytochemical tests confirmed the presence of terpenoids. The nanoemulsion showed enhanced physicochemical stability and uniformity compared to conventional suspensions. Conclusion: The formulated nanoemulsion-based syrup significantly improves the solubility and bioavailability of andrographolide. It holds promise as a stable, effective, and patient-friendly antiviral delivery system..